World Trade in Gold with Focus on Sanctions Against Russia - Divácká, Štěpánka; Bolotov, Ilya; Agustina, Shirley Basauli; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
The aim of this thesis is to examine the historical and current events in the world trade in gold, mainly in connection with Russia. The main research question is: How has the economic and political situation together with sanctions affected Russian trade in gold in the past 20 years? This thesis is divided into three chapters. First chapter provides an overview of the history and properties of gold together with the methodology, second chapter examines the global trade in gold, and the third chapter investigates the Russian economy and the impact of sanctions on the Russian trade in gold. The findings show that the 2014 sanctions did not affect the Russian trade in gold much but 2022 sanctions had an undeniable impact. The Russian gold exports shifted mainly towards Asian countries after the sanctions imposition. The thesis provides a building stone for future research on the development of the impacts of sanctions on the Russian trade in gold.
Vedoucí práce: Ilya Bolotov
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses